Fabrication and Functionalisation of Nanocarbon‐Based Field‐Effect Transistor Biosensors. (3rd November 2022) - Lee, Chang‐Seuk; Gwyther, Rebecca E. A.; Freeley, Mark; Jones, Dafydd; Palma, Matteo
Abstract: Nanocarbon‐based field‐effect transistor (NC‐FET) biosensors are at the forefront of future diagnostic technology. By integrating biological molecules with electrically conducting carbon‐based platforms, high sensitivity real‐time multiplexed sensing is possible. Combined with their small footprint, portability, ease of use, and label‐free sensing mechanisms, NC‐FETs are prime candidates for the rapidly expanding areas of point‐of‐care testing, environmental monitoring and biosensing as a whole. In this review we provide an overview of the basic operational mechanisms behind NC‐FETs, synthesis and fabrication of FET devices, and developments in functionalisation strategies for biosensing applications. Abstract : Next‐generation diagnostics : Nanocarbon‐based field effect transistors (NC‐FETs) use incoming target analytes to impart a gating effect on conductance. Here, we review the operational mechanisms behind NC‐FETs, the fabrication and functionalisation of NC‐FETs with receptor biomolecules and downstream biosensing applications.